Romans 8: A Discourse of Deification according to John Chrysostom - Elias, David-Ehab (2024)
In Pauline theology, Christ is the new Adam who annuls the effect of the Fall and grants humanity divine gifts. The centrality of Romans 8 in the New Testament and, more specifically, in the Pauline writings is unquestioned. In Romans 8, a unique relationship is established—all that Christ is and has done is given to humanity. Romans 8 reveals that God bestows the gifts of life, adoption, and glory on the faithful. These gifts culminate in the faithful’s conformity to the image of the Son of God. Prominent biblical scholars, each with their own focus, have established the significance of the themes of life, adoption, and glory in Romans 8. This article discusses the opinions of several scholars on these three themes in this chapter. John Chrysostom (ca. 349–407 CE) offers a detailed and eloquent exegesis of Romans 8. This article examines Chrysostom’s commentary on these themes and discusses the faithful’s conformity to the Son of God as discussed by Chrysostom and modern biblical scholars. Moreover, the article assesses the tenet of modern theological scholars who consider that Paul’s rhetoric in Romans 8 implicitly speaks of deification. The article argues that despite the paucity of technical language, Chrysostom speaks of deification in his commentary on the chapter.
Keywords: John Chrysostom; Theosis; Deification; Glory; Adoption; Life; Sonship; Romans 8